2022
DOI: 10.3390/cells11152380
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Acetylomics Uncover Acetylation-Mediated Pathway Changes Following Histone Deacetylase Inhibition in Anaplastic Large Cell Lymphoma

Abstract: Histone deacetylases (HDACs) target acetylated lysine residues in histone and non-histone proteins. HDACs are implicated in the regulation of genomic stability, cell cycle, cell death and differentiation and thus critically involved in tumorigenesis. Further, HDACs regulate T-cell development and HDAC inhibitors (HDACis) have been approved for clinical use in some T-cell malignancies. Still, the exact targets and mechanisms of HDAC inhibition in cancer are understudied. We isolated tumor cell lines from a tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…For example, functional dysregulation of histone acetyltransferases has been associated with cancer development, including B-cell [45,46] and T-cell lymphomas [47,48]. In humans, histone modifier gene mutations have been associated with inferior progression-free survival time in patients with T-cell lymphomas [48], and it has been demonstrated that HDAC regulates the expression of BCL6, involved in cell survival and/or differentiation in B-cell lymphoma [49], and HDAC inhibitors have been tried as therapy in humans [50][51][52]. In CML, repression of p16 tumour suppressor gene is regulated by histone H3 acetylation in vitro [53].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…For example, functional dysregulation of histone acetyltransferases has been associated with cancer development, including B-cell [45,46] and T-cell lymphomas [47,48]. In humans, histone modifier gene mutations have been associated with inferior progression-free survival time in patients with T-cell lymphomas [48], and it has been demonstrated that HDAC regulates the expression of BCL6, involved in cell survival and/or differentiation in B-cell lymphoma [49], and HDAC inhibitors have been tried as therapy in humans [50][51][52]. In CML, repression of p16 tumour suppressor gene is regulated by histone H3 acetylation in vitro [53].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Additionally, HDACs target non-histone proteins and changes in overall protein acetylation might contribute to the observed phenotype. Indeed, in a previous study we identified several hundred differentially acetylated proteins, including chromatin modifying proteins and transcription factors, in mouse NPM-ALK tumor cell lines depleted for HDAC1, using quantitative acetylomics 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Snap-frozen tissues were lysed in Hunt buffer and processed for SDS-PAGE and Western blot analysis as previously described 15 . Antibodies and buffers are listed in Supplementary Methods.…”
Section: Protein Isolation Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-collection, the pellets were snap-frozen and subsequently stored at -80°C. Protein isolation and western blotting was carried out as described earlier (51), with minor deviations: 10 µg Protein was used for each blot and BSA was used for blocking of membranes. Antibodies used are provided in SI supplementary table 3.…”
Section: Protein Isolation and Western Blottingmentioning
confidence: 99%